Secrets we tell the sea - Palacio Obon, Martha Riva; Heuer, Lourdes (New York Bloomsbury Children's Books, 2023)
When hard truths come out after a tragedy, ten-year-old mermaid Sofia must learn how to forgive herself and others.
Ages 8-11.
Grades 4-6.
112469
Keywords: Mermaids -- Juvenile fiction; Fishes -- Juvenile fiction; Families -- Juvenile fiction; Islands -- Juvenile fiction; Friendship -- Juvenile fiction; Fantasy; Fantasy fiction; Novels; Romans